2010
DOI: 10.1002/pbc.22853
|View full text |Cite
|
Sign up to set email alerts
|

The Saint Siluan warning signs of cancer in children: Impact of education in rural South Africa

Abstract: Two thirds of children with cancer never reach a specialist centre for treatment in South Africa. The majority of those who present have advanced disease. A campaign was undertaken to educate the public and the primary health workers on the Saint Siluan early warning signs of cancer in children. There was a statistically significant increase in the number of new patients referred in the 6 years following the campaign (P = 0.001), but did not succeed in achieving the referral of patients at earlier stages of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 1 publication
0
51
0
1
Order By: Relevance
“…Delay is invariably the cause of increased mortality rates in resource-poor countries; reports from African countries including the Democratic Republic of Congo, Nigeria, Tanzania, Mali, South Africa, and Kenya demonstrate this [2,5,6,11,12,13,14,15,16]. The average delay to presentation in our population was 7.0 months, which is lower than that reported earlier from Johannesburg by Poyiadjis et al [16] in 2011 (10.1 months) but similar to that in other African populations, where delays generally in excess of 6 months and up to 15 months have been reported [2,6,14,16]. Nyamori et al [13] found that in Kenya, even patients with a family history of retinoblastoma had a delayed presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delay is invariably the cause of increased mortality rates in resource-poor countries; reports from African countries including the Democratic Republic of Congo, Nigeria, Tanzania, Mali, South Africa, and Kenya demonstrate this [2,5,6,11,12,13,14,15,16]. The average delay to presentation in our population was 7.0 months, which is lower than that reported earlier from Johannesburg by Poyiadjis et al [16] in 2011 (10.1 months) but similar to that in other African populations, where delays generally in excess of 6 months and up to 15 months have been reported [2,6,14,16]. Nyamori et al [13] found that in Kenya, even patients with a family history of retinoblastoma had a delayed presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Kruger et al [12] reported on the outcomes of children with retinoblastoma in South Africa prior to (1993-2000) and after (2001-2008) the introduction of such healthcare initiatives and found that, while not statistically significant, there was a trend towards more limited disease and better survival in the latter period of the study [12]. A further initiative by the National Department of Health and the Childhood Cancer Foundation in 2001 involved a 6-month awareness campaign of the warning signs of childhood cancer directed at primary healthcare workers and the public in the North West and Gauteng provinces [12,16]. This campaign resulted in an increase in the number of new referrals to the Baragwanath oncology unit, but did not impact the advanced disease stages seen at presentation [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, pre-clinical screening modalities and interventions currently available for pediatric tumors are limited, and historically have not improved survival outcomes, particularly for biologically unfavorable or advanced-stage disease [19]. Community education programs have been able to reduce lag time of clinical presentation in developing countries, but have also not yielded sustained impact on survival outcomes [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…[10] The joint South African Children Cancer Study Group and NDoH awareness campaign distributed posters depicting the danger signs of childhood cancer to all primary care clinics, district and regional hospitals, as well as central hospitals in the country.…”
Section: Patient Groupsmentioning
confidence: 99%
“…[7][8][9] The National Department of Health (NDoH) and the Childhood Cancer Foundation (CHOC), acting in collaboration, introduced an awareness programme with posters depicting the danger signs of childhood cancer in primary healthcare clinics in 2000. [10] Doctors from the universities of the Witwatersrand and Pretoria also undertook outreach visits to referral hospitals in 2001 -2004 to train staff in early detection of childhood cancer, and especially to check for the absence of a red reflex in the eye in order to detect RB early. Parents were encouraged to note absent red reflex of an eye in photos taken with a flashlight.…”
mentioning
confidence: 99%